Evidence-based policy making in the social sciences : methods that matter - Stoker, Gerry; Evans, Mark, 1965 February 17- (Policy Press, 2016)
Drawing on the insights of some of the world's leading authorities in public policy analysis, this important book offers a distinct and critical showcase of emerging forms of discovery for policy-making. Chapter by chapter this expert group of social scientists showcase their chosen method or approach, showing the context, the method's key features and how it can be applied in practice, including the scope and limitations of its application and value to policy makers. Arguing that it is not just econometric analysis, cost benefit or surveys that can do policy work, the contributors demonstrate a range of other methods that can provide evidenced-based policy insights and how they can help facilitate progressive policy outcomes. The book will be ideal for upper level undergraduate students as well as Public Policy post-graduates, and can be used as the basis of an intensive learning experience for policy makers.-- Provided by publisher.
"This book emerged out of a conference that took place on Thursday 19 and Friday 20 February 2015 at Old Parliament House, Canberra, Australia"--Page xiii
Keywords: Policy sciences -- Congresses.; Social sciences -- Congresses.; Sciences de la politique -- Congrès.; Sciences sociales -- Congrès.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- Public Affairs & Administration.; Policy sciences; Social sciences; Politischer Prozess.; Forschungsmethode.; Sozialwissenschaften.; Politische Entscheidung.; Electronic books.; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.